2019
DOI: 10.1002/mbo3.821
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of community assembly in the developing chicken microbiome reveal rapid primary succession

Abstract: The fine‐scale temporal dynamics of the chicken gut microbiome are unexplored, but thought to be critical for chicken health and productivity. Here, we monitored the fecal microbiome of healthy chickens on days 1–7, 10, 14, 21, 28, and 35 after hatching, and performed 16S rRNA amplicon sequencing in order to obtain a high‐resolution census of the fecal microbiome over time. In the period studied, the fecal microbiomes of the developing chickens showed a linear‐log increase in community richness and consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 40 publications
13
111
2
Order By: Relevance
“…Some have found no difference in abundance at time points from 8 to 36 d.p.h while others have observed a decrease in Lactobacillaceae between 4 and 16 d.p.h (28,46). A similar pattern of succession to that described in this study has been proposed by Jurburg et al (25) after examining the fecal microbiome of chickens between 1 and 35 d.p.h although many taxa detected are associated with the caecal microbiome rather than the ileal microbiome. The first stage was dominated by rapidly-colonizing taxa such as Streptococcus and Escherichia/Shigella.…”
Section: General Pattern Of Successionsupporting
confidence: 87%
See 2 more Smart Citations
“…Some have found no difference in abundance at time points from 8 to 36 d.p.h while others have observed a decrease in Lactobacillaceae between 4 and 16 d.p.h (28,46). A similar pattern of succession to that described in this study has been proposed by Jurburg et al (25) after examining the fecal microbiome of chickens between 1 and 35 d.p.h although many taxa detected are associated with the caecal microbiome rather than the ileal microbiome. The first stage was dominated by rapidly-colonizing taxa such as Streptococcus and Escherichia/Shigella.…”
Section: General Pattern Of Successionsupporting
confidence: 87%
“…This likely explains the wide variety of results obtained by different groups when examining the intestinal microbiota in day-old chicks. In general, the initial microbiome is dominated Enterobacteriaceae or Clostridiaceae, although there are reports of high abundance other taxa such as Streptococcaceae and Enterococcaceae (3,20,24,25). At the genus level, the most commonly isolated Enterobacteriaceae are Escherichia/Shigella while Clostridiaceae are most often assigned to Clostridium sensu stricto 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in our study, birds may have had more access to litter, thereby influencing the GIT bacterial community composition. Additionally, we did not isolate any Bacteroidetes spp., which may be due to the production setting and animal diets, as well as the breed and age of the birds used (Zou et al 2018;Jurburg et al 2019). If the goal is the isolation of Bacteroidetes spp.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that even when birds were raised under similar conditions and on the same diet, a large degree of variation was observed within the cecal microbiota. In another study using culture-independent analysis, a succession of bacteria was observed in the fecal material of developing chicks, including a shift in the community structure from one dominated by class Alphaproteobacteria to one dominated by classes Bacteroidia and Clostridia (Jurburg et al 2019). These studies were able to ascertain limited information on activity.…”
Section: Introductionmentioning
confidence: 99%